Exchange Rate Bands and Shifts in the Stabilization Policy Regime : Issues Suggested by the Experience of Colombia - Carrasquilla, Alberto (IMF Working Papers; Working Paper, 1995)
After 25 years, the Colombian authorities decided to abandon the crawling peg exchange rate policy and implement a regime of nominal exchange rate bands. Initial conditions in Colombia contrast sharply with those of other cases in which bands were part of an ongoing effort to reduce high inflation. This paper argues that the change in regime was motivated by a change in policy objectives. Starting from a policy whose rationale implied targeting stable inflation, a simple analytical model of optimal policy is presented; initial results with the new regime suggest that inflation is now considered costlier and that policy implementation has been consistent with this new view.